Modulation of antibacterial activity of actinomycetes by co-culture with pathogenic bacteria - Haque, Md Uzzal; Rahman, Md Ajijur; Haque, Md Anwarul; Sarker, Ashish Kumar; Islam, Md Anwar Ul (Bangladesh Pharmaceutical Journal, 2015)
In this study, we investigated the effect of pathogenic bacteria on the production of antibiotics by actinomycetes. We used four strains of actinomycetes-ANAM-5, ANAM-39, AIAH-10 and ANTS-1, which were isolated from the soils of Sundrabans, Bangladesh. All the strains were cultured in absence or presence of either alive or heatkilled human pathogens (Staphylococcus aureus and E. coli). The antibacterial activity of cultured cell-free supernatant fluid was analyzed by disc diffusion assay against the inducer strains. Three out of the four marine actinomycetes tested showed enhanced antibacterial activity against Staphylococcus aureus and E. coli. ANAM-5 and AIAH-10 showed enhanced antibacterial activity when co-cultured with Staphylococcus aureus whereas ANAM-5 and ANAM-39 showed enhanced antibacterial activity when co-cultured with E. coli. The highest enhancement of antibacterial activity was exhibited by the strain ANAM-5 against Staphylococcus aureus (from 9 mm to 18 mm inhibition zone). The study has important ecological and biotechnological implications in case of microbial competition in the natural environment and may become helpful to discover novel classes of antibiotics with high specificity and huge production. Bangladesh Pharmaceutical Journal 18(1): 61-65, 2015